Women’s Satisfaction with Body Image before Pregnancy and Body Mass Index 4 Years after Delivery in the Mothers of Generation XXI - Henriques, Ana; Alves, Elisabete; Barros, Henrique; Azevedo, Ana (PLOS ONE, 2013)
Background Body image satisfaction (BIS) influences body weight regulation and may contribute to long-term healthier lifestyle after pregnancy. Thus, we aimed to assess the association between BIS before pregnancy and body mass index (BMI) 4 years after the index pregnancy. Methods As part of the follow-up of a birth cohort, 3612 women with prepregnancy BMI >18.5 kg/m2 were reevaluated 4 years after the birth of a child. BIS was defined as the difference between perceived and ideal body size before pregnancy, assessed by Stunkard Silhouettes after birth. The associations of BIS with BMI change (continuous) and BMI classes at 4 years, based on measured weight and height, were estimated using linear and multinomial regression, respectively. Results Among women with normal prepregnancy BMI, those who felt too small, regarding their ideal, had a 0.25 kg/m2 smaller increase in BMI within 4 years and a lower likelihood of becoming overweight or obese [multivariate-adjusted odds ratio (OR) = 0.63; 95% confidence interval (95%CI): 0.44–0.91 and OR = 0.21; 95%CI: 0.05–0.91, respectively) than those satisfied with body image. Feeling too large was associated with a 0.41 kg/m2 larger increase in BMI and a higher risk of becoming overweight or obese (OR = 2.12; 95%CI:1.73–2.59 and OR = 3.42; 95%CI:2.02–5.79, respectively). A similar, non-significant, trend was observed for overweight women. Obese women who felt too large had a non-significant decrease in BMI. Conclusions BIS plays a role in maternal body weight after delivery. Realistic body size goals may promote the motivation to lose weight and contribute to higher success in attaining them.